2012
DOI: 10.1158/1535-7163.mct-12-0021
|View full text |Cite|
|
Sign up to set email alerts
|

Obatoclax Interacts Synergistically with the Irreversible Proteasome Inhibitor Carfilzomib in GC- and ABC-DLBCL Cells In Vitro and In Vivo

Abstract: Interactions between the the irreversible proteasome inhibitor carfilzomib (CFZ) and the pan-BH3 mimetic obatoclax (Obato) were examined in GC- and ABC-DLBCL cells. Co-treatment with minimally toxic concentrations of CFZ (i.e., 2–6 nM) and sub-toxic concentrations of obato (0.05–2.0μM) synergistically increased apoptosis in multiple DLBCL cell lines and increased lethality toward primary human DLBCL but not normal CD34+ cells. Synergistic interactions were associated with sharp increases in caspase-3 activatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 47 publications
(94 reference statements)
0
27
0
Order By: Relevance
“…Parallel studies were performed in previously described bortezomib-resistant DLBCL and MCL cells (21, 29, 31). Whereas ricolinostat or CFZ were minimally toxic to SUDHL16-10BR, OCY-LY7-40BR (GC-DLBCL), or Granta-25BR (MCL) cells individually, combined treatment sharply increased cell death (Supplementary Fig 6A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Parallel studies were performed in previously described bortezomib-resistant DLBCL and MCL cells (21, 29, 31). Whereas ricolinostat or CFZ were minimally toxic to SUDHL16-10BR, OCY-LY7-40BR (GC-DLBCL), or Granta-25BR (MCL) cells individually, combined treatment sharply increased cell death (Supplementary Fig 6A).…”
Section: Resultsmentioning
confidence: 99%
“…In vivo experiment was carried out as described (31) and detail methods are presented in supplementary methods…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies showed that some bortezomib-resistant cell lines (Kuhn et al, 2009) and patients (Vij et al, 2012) were responsive to carfilzomib. Carfilzomib induced apoptosis by activation of pJNK (Dasmahapatra et al, 2012); in this study we tested the effect of the combination of BYL719 with carfilzomib on the proliferation and apoptosis of MM cells, and found that the drugs synergize through activation of p-JNK and induction of more caspase and PARP cleavage in MM cells.…”
Section: Discussionmentioning
confidence: 96%
“…One such agent is obatoclax (OBX), a synthetic indolylprodigiosin derivative that was shown to bind to Bcl-2, Bcl-xL, Bcl-w and Mcl-1 [19][20][21]. Preclinical studies have shown that OBX is effective as a single agent against a broad range of cancer cell lines and xenografts [22] and that it synergizes with a number of cytotoxic and targeted anticancer agents [23][24][25][26][27][28][29]. Clinical activity and tolerability have been assessed in a number of phase I and II trials (clinicaltrials.gov).…”
Section: Introductionmentioning
confidence: 99%